2016
DOI: 10.1002/oby.21725
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes prevalence is associated with different community factors in the diabetes belt versus the rest of the United States

Abstract: Objective This study investigated differences in community characteristics associated with diabetes prevalence between the Diabetes Belt and the rest of the contiguous U.S. Methods We used county-level adult diabetes prevalence estimates (i.e., percent of people [≥20 years] with diagnosed diabetes, 2009) from the Centers for Disease Control and Prevention, in addition to data from the U.S. Census Bureau, U.S. Department of Agriculture, and U.S. Department of Health and Human Services, to carry out a spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 32 publications
2
37
0
Order By: Relevance
“…Four studies did not observe an association between density of facilities and T2DM risk/prevalence [ 46 , 48 , 49 , 61 ]. In two other studies, the higher availability of neighbourhood resources for physical activity was associated with lower T2DM risk [ 47 , 63 ].…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Four studies did not observe an association between density of facilities and T2DM risk/prevalence [ 46 , 48 , 49 , 61 ]. In two other studies, the higher availability of neighbourhood resources for physical activity was associated with lower T2DM risk [ 47 , 63 ].…”
Section: Resultsmentioning
confidence: 96%
“…Twenty studies investigated characteristics of the food environment [ 46 48 , 51 55 , 60 , 61 , 63 , 69 77 ] (Fig. 1 , Table 2 and Additional file 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that living in the Stroke Belt during childhood may confer an additional risk for stroke, even after relocating out of the Stroke Belt [10]. Within the Stroke Belt is the "diabetes belt", characterized by a greater prevalence of diagnosed diabetes particularly among African Americans demonstrating modifiable risk factors such as obesity (as a result of a primarily sedentary lifestyle), as well as community -level characteristics, persistent poverty, low socioeconomic status (SES), unemployment and inadequate fitness and recreational facilities [11]. Characteristics of the Stroke Belt that may contribute to increased risk for diabetes are illustrated in Figure 1.…”
Section: The Stroke Beltmentioning
confidence: 99%
“…[8] Pathophysiology and prevention of CVD is also very complex as there are multiple risk factors besides obesity that could increase the risk. These risk factors include but are not limited to, smoking, alcohol and drug abuse along with HTN, DM2 and/or hyperlipidemia, which are all modifiable [9]. …”
Section: Introductionmentioning
confidence: 99%